Techno-economic analysis of a hybrid CO2 capture system for natural gas combined cycles with selective exhaust gas recirculation. (1st April 2018) - Diego, Maria Elena; Bellas, Jean-Michel; Pourkashanian, Mohamed
Highlights: A novel hybrid S-EGR configuration is analysed for CO2 capture in NGCC power plants. This system can lead to potential reductions in the size and cost of the capture plant. The S-EGR scheme is competitive in various scenarios against conventional options. This requires further advancements in membrane technology to reduce its cost. The potential benefits and development needs of hybrid S-EGR plants are highlighted. Abstract: This work analyses the implementation of CO2 capture in natural gas combined cycle (NGCC) power plants using a hybrid system integrated by an amine scrubbing plant and a CO2 selective membrane. In this configuration, the membrane unit operates at close to atmospheric pressure and it is used to selectively recycle CO2 back to the inlet of the compressor, therefore increasing the CO2 content of the flue gas entering the capture system. A novel integration between the amine capture plant and the selective membrane is analysed here, which aims at exploiting the benefits of both the parallel and series selective exhaust gas recirculation (S-EGR) existing options. The mass and energy balances performed on this system indicate that the new configuration generates a flue gas with a CO2 -enhanced concentration of 18%vol., which leads to a decrease in the energy demand in the reboiler by 6% with respect to an amine scrubbing system coupled to a conventional NGCC plant without S-EGR. Moreover, a reduction of 77% is achieved in the gas flowrate fed to the absorber of the amine plant, thus significantly reducing its size and cost. The calculated net electrical efficiency of the plant is 50.3%, which is 0.5 net percentage points higher than that of a conventional NGCC with amine-based capture and slightly lower than that of a reference plant with exhaust gas recirculation (EGR). These values are dependent on the pressure drop associated with the membrane system, which has a large influence on the energy balance of the plant. Therefore, higher efficiency improvements can be achieved if membrane module designs with reduced pressure drop are used. A techno-economic evaluation reveals that the cost of the membrane system has a strong effect on the capital costs of the plant and thus, on the cost of electricity and the cost of CO2 avoided. These values vary between 81.9 and 93.9 per MWh and 82.6 and 121.8 per tonne of CO2 avoided, respectively, for the S-EGR cases studied at a reference capacity factor of 0.85. A sensitivity analysis shows that it is necessary to reduce the costs of the reference hybrid S-EGR system in order to make it competitive against current benchmark options. Therefore, further ongoing development towards membrane units with high CO2 permeance, limited pressure drop and reduced costs is particularly interesting for the S-EGR system studied in this work. The obtained results also indicate the targeted values of these parameters that can make the cost of the S-EGR configuration to be below that of conventional systems with amine capture and EGR options for CO2 capture in NGCC power plants under different scenarios.